2013
DOI: 10.1177/0956462412473958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV genotypic drug resistance testing on the management and clinical course of HIV-infected children and adolescents

Abstract: The clinical utility of genotypic drug resistance testing (DRT) in HIV-infected children on antiretroviral therapy (ART) is not well understood. HIV-infected patients aged <19 years undergoing DRT for virological failure were retrospectively enrolled. Indications for DRT and changes in HIV RNA load were recorded. Between January 2000 and December 2006, 57 patients had DRT. The most common indication for DRT was poor ART adherence (57.7% of patients). ART was changed in 50.9% of patients after DRT. Poor adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Mutations associated with resistance to protease inhibitors occurred mainly at codons 54, 82 and 46, with rates of 35.4%, 32.3% and 27.7% respectively. The findings observed in the protease resistance profile were consistent with reports from other studies in children and adolescents in therapeutic failure, with prevalence ranging from 10%(Ramkinson et al, 2015) to 88.3%(Dehority et al, 2013). The susceptibility to darunavir/ritonavir (DRV/r) (96.9%) demonstrated in this study, favored therapeutic rescue in children and adolescents treated with several different ARV, presenting resistance to more than one class (Blanche et al, 2009; Salazar et al, 2014; Violari et al, 2015; Huibers et al, 2019), and was similar to that demonstrated in other studies (Rojas Sánchez et al, 2015).…”
supporting
confidence: 91%
“…Mutations associated with resistance to protease inhibitors occurred mainly at codons 54, 82 and 46, with rates of 35.4%, 32.3% and 27.7% respectively. The findings observed in the protease resistance profile were consistent with reports from other studies in children and adolescents in therapeutic failure, with prevalence ranging from 10%(Ramkinson et al, 2015) to 88.3%(Dehority et al, 2013). The susceptibility to darunavir/ritonavir (DRV/r) (96.9%) demonstrated in this study, favored therapeutic rescue in children and adolescents treated with several different ARV, presenting resistance to more than one class (Blanche et al, 2009; Salazar et al, 2014; Violari et al, 2015; Huibers et al, 2019), and was similar to that demonstrated in other studies (Rojas Sánchez et al, 2015).…”
supporting
confidence: 91%
“…While some studies report generally high adherence to ART (Barro et al, 2011; Haberer et al, 2011), others are as low as 49% (Vreeman, Wiehe, Pearce, & Nyandiko, 2008). Even in the studies with high adherence, low rates of viral suppression and the presence of drug resistance suggest current adherence assessments may be incorrect and/or important adherence challenges exist (Ahoua et al, 2011; Barro et al, 2011; Barth et al, 2011; Dehority, Deville, Lujan-Zilbermann, Spector, & Viani, 2013; Orrell et al, 2013). Accurate, reliable, and practical means of evaluating pediatric ART adherence are critical in overcoming these concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Effective combination antiretroviral (ARV) therapy (ART) leading to suppression of viral replication with improvements in immune status is associated with declining morbidity, hospitalization, and mortality rates in children infected with human immunodeficiency virus (HIV) type 1 (HIV-1) [1][2][3][4][5]. However, short and long-term toxic effects, poor adherence to ARV regimens, and lack of treatment alternatives due to HIV-1 resistance resulting from prior failing ARV regimens, local drug availability, and the paucity of appropriate pediatric fixed-dose combination tablets further complicates HIV-1 management and contributes to the development of additional drug resistance mutations [6][7][8][9]. The development of safe, palatable, and potent ARV regimens, particularly those that block alternative targets in the HIV-1 life cycle that have a high barrier to resistance, are critically important for all children and adolescents, especially those who have treatment failure or are unable to tolerate currently available ARVs.…”
mentioning
confidence: 99%